Functional analysis of Tb927.9.2900, a protein involved in pre-18S rRNA processing in Trypanosoma brucei - Bär, Anita (Jihočeská univerzita, 2017)
The aim of this thesis was to perform functional analysis of Tb927.9.2900 protein in Trypanosoma brucei and to verify whether this protein is involved in processing of pre-18S ribosomal RNA.
Functional analysis of Tb927.9.2900, a protein involved in pre-18S rRNA processing in Trypanosoma brucei